'Carried off in their hundreds': Epidemic diseases as structural violence among Indigenous peoples in Northwestern Australia. Issue 4 (7th August 2020) - Smith, Nicholas
ABSTRACT: As in several other settler colonial societies, Australia has come some way to recognising the suffering inflicted upon its First Peoples as a consequence of colonisation. Such historical reassessment of the nation's origins has given rise to a backlash of unsettlement. Australia's History Wars feature claims and counter claims regarding the number of Aboriginal people intentionally murdered by colonists as distinct from 'unintentional' Indigenous fatalities resulting from introduced infectious diseases. Following recent critiques of the 'virgin soil' hypothesis in context of the Columbian Exchange (for example Cameron, Catherine M., Paul Kelton, and Alan C. Swedlund, eds. 2015. Beyond Germs: Native Depopulation in North America. Tucson: University of Arizona Press.), I argue that biological determinism has similarly obscured the violence of Australian settler colonialism. Focussing on observations of a mid-nineteenth century outbreak of smallpox in Australia's Northwest, I seek to expand the horizons of debates concerning the scope and extent of settler colonial violence to include the appraisal of introduced diseases as a form of structural violence.